1995
DOI: 10.1016/s0022-5223(95)70274-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of incomplete distribution of cardioplegic solution during coronary artery grafting

Abstract: Myocardial distribution of cardioplegic solution infused by combined antegrade/retrograde routes was assessed with myocardial contrast echocardiography in 18 patients with chronic stable angina and three-vessel disease undergoing elective coronary artery bypass grafting. Overall myocardial opacification was significantly greater in retrograde than in antegrade cardioplegia (77.7% +/- 13.4% versus 59.1% +/- 15.7%; p = 0.0009). The difference was affected by collateral circulation, as pointed out by the signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 50 publications
(15 reference statements)
0
10
0
1
Order By: Relevance
“…Kardiyoplejinin antegrad ya da retrograd verilmesindeki dezavantajlar, cerrahın ameliyat sırasındaki kardiyopleji kullanım tercihinde önemli rol oynamaktadır. Aort yetmezliği, ciddi proksimal koroner arter lezyonları ve redo olgulardaki önceki greftler, antegrad kardiyopleji kullanımını kısıtlayabilir (9) . Antegrad aralıklı 20 şer dakikalık kardiyopleji uygulamaları, total perfüzyon zamanını ve aortik kros klemp süresini de uzatmaktadır.…”
Section: Discussionunclassified
“…Kardiyoplejinin antegrad ya da retrograd verilmesindeki dezavantajlar, cerrahın ameliyat sırasındaki kardiyopleji kullanım tercihinde önemli rol oynamaktadır. Aort yetmezliği, ciddi proksimal koroner arter lezyonları ve redo olgulardaki önceki greftler, antegrad kardiyopleji kullanımını kısıtlayabilir (9) . Antegrad aralıklı 20 şer dakikalık kardiyopleji uygulamaları, total perfüzyon zamanını ve aortik kros klemp süresini de uzatmaktadır.…”
Section: Discussionunclassified
“…There have been reports which document cases that showed retrograde perfusion to be less efficient than antegrade perfusion in protecting normal regions of the myocardium (8,9). There is a report that documents cases that showed hypoperfusion of the right ventricle to be one of the causes of the right ventricle failure (10).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical studies have demonstrated that critical stenosis of the coronary arteries may prevent homogenous distribution of cardioplegic solution when it is injected through the aortic root, which may contribute to the higher incidence of perioperative myocardial infarction observed in such patients. [17][18][19][20][21] Retrograde coronary sinus perfusion was first introduced by Lillehei and colleagues 22 in 1956 to facilitate surgery on the aortic valve. In the late 1970s, interest emerged in the coronary sinus as a route for delivery of cardioplegia.…”
Section: Discussionmentioning
confidence: 99%